Spatial Learning and Memory in the Naked Mole-Rat: Evolutionary Adaptations to a Subterranean Niche - Hite, Natalee J.; Sudheimer, Keith D.; Anderson, Luke; Sarko, Diana K. (Frontiers in Ecology and Evolution, 2022)
Evolutionary adaptation to a subterranean habitat consisting of extensive underground tunnel systems would presumably require adept spatial learning and memory, however such capabilities have not been characterized in naked mole-rats (Heterocephalus glaber) which, like other members of Bathyergidae, are subterranean rodents. The goal of this study was to develop a method for effectively assessing spatial learning and memory by modifying a Hebb-Williams maze for use with these subterranean rodents. Established behavioral tests to assess spatial learning and memory have primarily focused on, and have been optimized for, more typical laboratory rodent species such as mice and rats. In the current study, we utilized species-appropriate motivators, analyzed learning curves associated with maze performance, and tested memory retention in naked mole-rats. Using a modified Hebb-Williams maze, naked mole-rats underwent three days of training, consisting of five trials per day wherein they could freely explore the maze in search of the reward chamber. Memory retention was then tested one day, one week, and one month following the last day of training. Performance was analyzed based on latency to the reward chamber, errors made, and distance traveled to reach the reward chamber. Overall, this study established a behavioral paradigm for assessing maze navigation, spatial learning, and spatial memory in subterranean rodents, including optimization of rewards and environmental motivators.